Mulheres no criptojudaísmo : o olhar da historiografia - Cruz, Camila Santos Muniz da (2015)
This article aims to demonstrate the role that women played in the constitution of Crypto. The aim is to demonstrate how the role of women is reversed in the secret Judaism. Show that when the Jews were expelled from Spain (1492) and Portugal (1496), and Jewish practices are banned and persecuted, their descendants, the New Christians, have developed a new type of Judaism in the midst of persecution, in which the new Christian woman had great performance in resistance. The role that women have in Judaism is of great importance for the survival of the Jewish religious practice, and attract the hungry eyes of the Inquisition that will condemn them without mercy. A Crypto, which as its name states is hidden, secret, where women in many cases had the lead role, that is, in most cases analyzed by historiography were protagonists. Knowing how the historiography portrays and how you report your presence makes us realize how important they were in the process of resistance New Christian culture Judaizing in Portuguese America. The cases studied show that although they were condemned by the Inquisition, women had various social positions and different ways to give you that extreme situation. The similar and the differences will be discussed below